Ottoman ulema, Turkish Republic agents of change and guardians of tradition - Bein, Amit (Stanford University Press, 2011)
To better understand the diverse inheritance of Islamic movements in present-day Turkey, we must take a closer look at the religious establishment, the ulema, during the first half of the twentieth century. During the closing years of the Ottoman Empire and the early decades of the Republic of Turkey, the spread of secularist and anti-religious ideas had a major impact on the views and political leanings of the ulema. This book explores the intellectual debates and political movements of the religious establishment during this time.Bein reveals how competing visions of development
Keywords: Ulama : Turkey : History : 20th century; Islam : Turkey : Functionaries : History : 20th century; Muslim scholars : Turkey : History : 20th century; Islam and state : Turkey : History : 20th century; Secularism : Turkey : History : 20th century; Turkey : History : Revolution, 1918-1923 : Religious aspects